Engagement of Fas differentially regulates the production of LPS‐induced proinflammatory cytokines and type I interferons. (22nd December 2018) - Brennan, Kiva; Lyons, Caitriona; Fernandes, Philana; Doyle, Sarah; Houston, Aileen; Brint, Elizabeth
Abstract : Fas (CD95) signalling is best known for its role in apoptosis, however, recent reports have shown it to be involved in other cellular responses as well, including inflammation. Fas and its adaptor protein FADD are known to negatively regulate LPS‐induced proinflammatory responses, but their role in LPS‐induced type I interferon production is unknown. Here, we demonstrate that Fas engagement on macrophages, using an agonistic Fas antibody CH11, augments LPS‐induced NF‐κB responses, causing increased production of TNFα, IL‐8, IL‐6 and IL‐12. Conversely, costimulation with both LPS and CH11 causes a significant reduction in the level of interferon‐beta (IFNβ) production. This differential effect involves the Fas adaptor FADD because while LPS‐induced IL‐6 production increased in FADD −/− murine embryonic fibroblasts, LPS‐induced IFNβ production was significantly reduced in these cells. Overexpression of a dominant negative form of FADD (FADD‐DD) inhibits LPS‐induced IFNβ luciferase but not LPS‐induced NF‐κB luciferase. In contrast, overexpression of full‐length FADD inhibited LPS‐induced NF‐κB luciferase activation but was seen to augment LPS‐induced IFNβ luciferase. Moreover, FADD‐DD inhibits TRIF‐, TRAM‐, IKKε‐, TBK‐1‐ and TRAF3‐induced IFNβ luciferase production, with coimmunoprecipitation experiments demonstrating an interaction between FADD and TRIF. These data identify FADD as a novel component of the noncanonical Toll‐like receptor 4/IFNβ signalling pathway and demonstrate that both Fas and its adaptor FADD can differentially regulate the production of LPS‐induced proinflammatory cytokines and type I interferons. Abstract : We have identified that the death receptor Fas and its adaptor protein FADD are able to differentially regulate the MYD88‐dependent and ‐independent arms of the TLR4 signalling pathway. FADD is a negative regulator of the MyD88‐dependent arm (A) but is an essential component of the MyD88‐independent pathway (B), facilitating induction of LPS‐induced IFN‐beta through an interaction with TRIF.